Diderot's 'Essai sur Sénèque' - Conroy, W (Voltaire Foundation, 2017)
Preface I. Background to Diderot's Essai sur Sénèque A. Classical studies in the eighteenth century B. The Tradition of Senecan studies C. The Expectation and reception of Diderot's Essai II. The Essai sur Sénèque as a defence of Seneca A. Diderot's adaptation of primary texts B. Diderot's reconstruction of history C. Refutation of the critics of Seneca III. The Essai sur Sénèque as a defence of Diderot A. Diderot's affinity with Seneca B. Further parallels between Seneca and Diderot C. The Character Seneca and apology IV. The Essai sur Sénèque as a didactic work A. Diderot's manner of instruction B. Diderot's thoughts on politics C. The Character Seneca and moral example V. The Essai sur Sénèque as literary work A. The Style of Diderot's translations B. The Structure of the Essai Conclusion List of works consulted